Rural-Urban Interactions: Potential or Constraint to Rural Development? Lessons from Western Bagamoyo District, Tanzania (Tanzania Journal for Population studies and Development, 2011)
This paper discusses the contribution of rural-urban interaction to rural development in western Bagamoyo, Tanzania, based on a study that was conducted in 2009. A sample of 232 households was drawn from five villages that have good transport linkage to Dar es Salaam and other intermediate towns. The study area has a long history of rural-urban interactions (RUIs). However, the potentials of RUIs are not realised due to the relatively marginal position of rural-urban migrants from the area that compels them to access low paying occupations in towns, and consequently limits their contribution despite having strong ties with their rural homes. The majority of migrants have very little to offer for rural development due to their low incomes in town. However, there are cases of successful migrants who have the potential to contribute to rural development through their own investment and influence. These should be targeted for collaboration with local communities. Whereas RUIs facilitate access to rural resources by urban dwellers, the rural to urban flow of resources often has limited benefits to rural communities due to weaknesses in valuation, taxation and allocation of revenues collected to local communities. In order to benefit from RUIs, policy and development planning should ensure the protection of interests of rural communities, as well as promote economic opportunities for rural-urban migrants.